PENGARUH PBL MENGGUNAKAN MEDIA LKS PADA MATERI PENCEMARAN LINGKUNGAN TERHADAP PEMECAHAN MASALAH DAN HASIL BELAJAR SISWA KELAS X SMA ISLAM YABADI BEBUAK - Neneng Agustiningsih (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2019)
This study aims to determine the effect of Problem Based Learning models on problem solving abilities and student learning outcomes. This research was conducted at Baiturrahman Mahmudi Islamic High School (Yabadi) Bebuak. The research method used is Pre-Experimental Design using One-Group Pretest-Posttest Design with a quantitative approach. Sampling was carried out using a saturated sample technique. The research sample consisted of 29 students of class X. Data collection using an instrument in the form of a test that was adjusted to the indicators of problem solving and the cognitive domain of learning outcomes and had been tested for validity, and reliability, as well as observation sheets for the implementation of learning. The results showed that the average post-test score of problem solving ability was 80.00, while the post-test average score of 65.21. Data analysis using t-test, obtained t value for solving problems of 4.52 and for learning outcomes of 4.81 while the t table with a significance level of 5% (0.05) and degrees of freedom (dk) = 28 of 1.70 (t- count> t - table). Then it can be said that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The conclusion from the results of this study that there is an influence of the Problem Based Learning learning model on problem solving and student learning outcomes.